“They Stole All My Shit”: A Qualitative Exploration of By-Law Practices and People Experiencing Homelessness - Mitra Mokhtari; Carolyn Greene; Katharina Maier; Marta-Marika Urbanik (Socius)
Drawing on interviews with 65 people experiencing homelessness (PEH) in Victoria, British Columbia (Canada), this article examines the role and impact of municipal by-laws’ daily governance of PEH and their possessions. We argue PEH’s possessions are a site of governance that by-law officers use to exert both punitive control and responsibilization onto PEH’s lives. We show how the daily governance of possessions enhances and reinforces existing strategies of displacement and motion and illuminate how forms of governance tied to the movement of PEH can be simultaneously experienced as both routinized and random when subjectively enforced.